Biocatalytic Production of Ethyl Esters (Biodiesel) by Enzymatic Transesterification from Synthetic Triolein - G. Rosset, Isac; M. Assaf, Elisabete; L.M. Porto, Andre (Current Catalysis, 2013)
We investigated an efficient production of ethyl esters (biodiesel) by enzymatic transesterification of triolein. This triacylglyceride was synthesized from oleic acid and glycerol by acid catalysis and then subjected to enzymatic transesterification by Candida antarctica lipase. This biocatalytic process afforded high yields of biodiesel (93% by 1H NMR, 90.4% by GC, 24 h, at 32 °C) which were dependent on reaction time. The yield of biodiesel was determined by 1H NMR and GC-FID analyses. The 1H NMR methodology developed for the quantification of biodiesel in unpurified reaction mixtures showed good correlations between the signal areas of peaks associated with the -methylene protons of the triolein (δ2.31) and those of the ethyl oleate ( δ2.28) in residual oil. Monoacyloleate (MAO), diacyloleate (DAO) and triacyloleate (TAO) could also be detected and quantified in the crude biodiesel using 1H NMR spectroscopic and GC-FID chromatographic methods. The enzymatic transesterification produced low amounts of monoacyloleate (2-MAO, 0.8% by GC) and diacyloletate (1,2-DAO, 1.3% by GC). Another advantage of the biocatalytic reaction was the production of high purity glycerol that was easily removed by decanting.
Keywords: GC